Pengaruh Prokrastinasi Akademik terhadap Hasil Belajar Mata Pelajaran Akidah Akhlak Siswa Kelas VIII di Sekolah Menengah Pertama Birrul Walidain Muhammadiyah Kabupaten Sragen Tahun Pelajaran 2023/2024 - Amalia Pratiwi; Nur Hidayah; Sugiyat Sugiyat (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study employs a quantitative-correlational approach to investigate academic procrastination among 8th-grade students at Birrul Walidain Muhammadiyah Junior High School in Sragen Regency for the academic year 2023/2024. It aims to assess the level of academic procrastination, determine the learning outcomes of Akidah Akhlak subjects, and explore the impact of academic procrastination on these outcomes. Conducted at the aforementioned school, the research sampled 52 students and utilized both questionnaire responses and Akidah Akhlak scores for data collection. Findings reveal that the highest level of academic procrastination, at 33%, falls within the 28-32 score interval, while the lowest, at 0%, is observed in the 53-57 score interval. Similarly, the highest learning outcomes in the Akidah Akhlak subject, at 33%, are within the 85-89 score interval, whereas the lowest, also at 0%, are found in the 100-104 score interval. Hypothesis testing indicates a significant relationship, with an r count of 0.428 surpassing the r table value of 0.268. This correlation coefficient of 0.428 signifies a moderate level of relationship/influence between academic procrastination (variable X) and Akidah Akhlak learning outcomes (variable Y).